2008
DOI: 10.1002/jclp.20536
|View full text |Cite
|
Sign up to set email alerts
|

A meta‐analysis of the effects of internet‐ and computer‐based cognitive‐behavioral treatments for anxiety

Abstract: Internet-and computer-based cognitive-behavioral treatments have been introduced as novel approaches to deliver standard, quality treatment that may reduce barriers to care. The purpose of this review is to quantitatively summarize the literature examining the treatment effects of Internet- or computer-based treatment (ICT) on anxiety. Nineteen randomized controlled ICT trials were identified and subjected to fixed and random effects meta-analytic techniques. Weighted mean effect sizes (Cohen's d) showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
138
0
5

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(151 citation statements)
references
References 38 publications
(28 reference statements)
7
138
0
5
Order By: Relevance
“…Randomized controlled trials (RCTs) investigating Internet-delivered CBT differ with respect to the type of control group, the degree of therapist involvement, the types of communication and the format of the online modules, which makes it difficult to compare their findings. 8,9 In addition to evidence from these RCTs, we also incorporate literature on smartphone and tablet apps.…”
Section: What Is the Evidence For Internetdelivered Cbt?mentioning
confidence: 99%
“…Randomized controlled trials (RCTs) investigating Internet-delivered CBT differ with respect to the type of control group, the degree of therapist involvement, the types of communication and the format of the online modules, which makes it difficult to compare their findings. 8,9 In addition to evidence from these RCTs, we also incorporate literature on smartphone and tablet apps.…”
Section: What Is the Evidence For Internetdelivered Cbt?mentioning
confidence: 99%
“…For instance, Reger and Gahm showed that a significant number of individuals preferred ICT to walking into a counselling centre [60]. They suggested that assumptions that a therapist was preferred over ICT might be inaccurate for significant …”
Section: Complexity and Contexts -Fitting The Objects/subjects Of Stumentioning
confidence: 99%
“…For this purpose, controlled action research was proposed. Reger and Gahm [60], stated that ICT could be useful as a tool to explore the essential components of CBT as it would allow researchers to add, modify or delete specific components while leaving others unchanged for a comparison group. The intention should be to refine CBT theory and practice.…”
Section: Action Researchmentioning
confidence: 99%
“…3,4 In recent years, computerized psychotherapy (CP), which involves self-directed learning of therapeutic concepts and skills through online or other technological platforms, has gained recognition as one potential solution to the rift between evidence-based therapies and community practice. [5][6][7][8] CP programs can be easily distributed to anyone with a computer and/or Internet connection, remain at absolute fidelity to their underlying treatment models, do not tire or burnout, can be easily updated and redisseminated as new findings emerge, and can be accessed at places and times convenient for consumers. In this way, CP is analogous to psychotropic medication in that its initial development and testing can result in swift marketing to a widespread consumer base with minimal cost to the developer.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] To date, 10 meta-analyses have been published indicating the feasibility, acceptability, and efficacy of CP. [6][7][8]12,[16][17][18][19][20][21] However, researchers cannot assume that treatment effects demonstrated in controlled trials with carefully selected participants will generalize to the larger, more complex population to which treatments may ultimately be disseminated, 22 and this is particularly troublesome given the ease of dissemination of cCBT. Along those lines, recent research has criticized the treatment utility of cCBT for depression, noting that cCBT does not produce long-term maintenance of treatment gains and demonstrates considerably high dropout rates.…”
Section: Introductionmentioning
confidence: 99%